Theoretical-Methodological Aspects and Empirical Study of Internal Pattern of Disease in Clinical Psychology - Kykhtuik, Oksana (Psychological Prospects Journal, 2018)
The article deals with theoretical and methodological analysis of recent studies of the phenomenon of the internal picture of the disease in domestic and foreign literature. An attempt was made to summarize the main scientific approaches to understanding this concept. The role of the clinical psychologist in the research and description of this phenomenon is determined. The main definitions of the concept of the internal picture of the illness are substantiated, its structure, types of reactions and the patient’s response to his illness are described. The most well-known methods of studying the internal picture of illness, which are used for the study of cardiovascular diseases by students, psychologists, counselors, psychotherapists in their practice are considered. We have developed and described in this article the contents of the questionnaire in the form of unfinished allegations. It can serve as an additional tool in the clinical practice of a psychologist, as a psycholinguistic tool. We carried out a pilot study of the internal picture of the disease in people with chronic kidney disease (chronic pyelonephritis with renal insufficiency). The respondents identified the main aspects of the subjective attitude to the illness in the basis of the emotional, cognitive, motivational and regulatory sphere of the individual. Phenomenon of the internal picture of the disease in patients with chronic kidney disease appears in the form of adaptation with negative experiences associated with it, the development of certain coping strategies of behavior, response to the prescriptions of the doctor.